2011
DOI: 10.1007/s11255-011-0010-2
|View full text |Cite
|
Sign up to set email alerts
|

Urodynamically diagnosed detrusor hypocontractility: should transurethral resection of the prostate be contraindicated?

Abstract: UDs may play a very limited role in detecting bladder outlet obstruction (BOO) in BPH patients with hypocontractile detrusor. TURP may obtain a promising effect on such patients with unidentified BOO. These patients should not be arbitrarily excluded from surgical indications simply based on UDs findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 20 publications
0
40
0
Order By: Relevance
“…Previous studies also suggested that men with DU have significantly improved Q max and PVR after transurethral resection of the prostate. 10,11 Endoscopic incision of the bladder neck for patients with bladder neck dysfunction was first reported by TurnerWarwick et al 12 in 1973. Choudhury 13 also reported on nine women with bladder neck obstruction who received TUI-BN.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also suggested that men with DU have significantly improved Q max and PVR after transurethral resection of the prostate. 10,11 Endoscopic incision of the bladder neck for patients with bladder neck dysfunction was first reported by TurnerWarwick et al 12 in 1973. Choudhury 13 also reported on nine women with bladder neck obstruction who received TUI-BN.…”
Section: Discussionmentioning
confidence: 99%
“…[6] Detrusor underactivity is considered a poor predictor of outcome after TURP[7] though some authors have reported the beneficial results of TURP in patients with underactive detrusor. [8910] Detrusor failure occurs secondary to long-standing outflow obstruction leading to damage of innervation or the ultrastructure morphology of detrusor muscle. [11]…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that TURP should not be a contraindication merely based on the urodynamic finding of DU. The study sample is very small however [45].…”
Section: Benign Prostatic Hyperplasiamentioning
confidence: 99%